Nivolumab in Resected and Unresectable Metastatic Melanoma: Characteristics of Immune-Related Adverse Events and Association with Outcomes - Freeman-Keller, Morganna (Clin Cancer Res, 2015)
PURPOSE: Retrospective analysis of irAEs in melanoma patients treated with nivolumab. EXPERIMENTAL DESIGN: Data were pooled from 148 patients (33 resected, 115 unresectable) treated with nivolumab plus peptide vaccine or nivolumab alone every 2 weeks for 12 weeks. Patients with stable disease or regression received an additional 12-week cycle, then nivolumab alone every 12 weeks for up to 2 additional years. Frequency, grade, and characteristics of irAEs were analyzed. A 12-week landmark survival analysis using a multivariate time-dependent Cox proportional hazard model assessed difference in OS in the presence or absence of irAEs. RESULTS: IrAEs of any grade were observed in 68.2% of patients (101 of 148). Grade III/IV irAEs were infrequent: 3 (2%) had Grade III rash, 2 (1.35%) had asymptomatic Grade III elevation in amylase/lipase, and 2 (1.35%) had Grade III colitis. A statistically significant OS difference was noted amongst patients with any grade of irAE versus those without (p=<0.001), and OS benefit was noted in patients who reported 3 or more irAE events (p=<0.001). Subset analyses showed statistically significant OS differences with rash (p=0.001 [HR 0.423, 95% CI 0.243 to 0.735]) and vitiligo (p=0.012 [HR 0.184, 95% CI 0.036 to 0.94]). Rash and vitiligo also correlated with statistically significant OS differences in patients with metastatic disease (p=0.004 and p=0.028, respectively). No significant survival differences were seen with other irAEs (endocrinopathies, colitis, or pneumonitis). CONCLUSIONS: Cutaneous irAEs are associated with improved survival in melanoma patients treated with nivolumab, and clinical benefit should be validated in larger prospective analyses.